DEKONSTRUKSI DIRI SENDIRI DALAM PROSES PENCIPTAAN KARYA SENI - Ign. Hening Swasono Ph (Imaji, 2007)
Self deconstruction is a means of breaking down the established art creation, representing individual identity and abandoning modern art or conventional art creation. It was applied in a work of art, whose forms were cracked wood constructed like paintings. In the new concept of art creation, self-deconstruction of Derrida and Nagajurna was applied. The deconstruction as a concept of creating and acting bravely to break down reality and imitating self creation was applied until the zero point. In other words, the emptiness is stability. “All possible” is the concept of creation applied by the writer. The concept was realized by using used wood as a medium of expression of artistic moments. The installation was composed of several different media such as wood, plastic and iron. The concept also abandoned single medium (the modern view of art creation). This art creation used the integration of creation and recreation as well. The creation technique applied was assemblage, collage, and knockdown system with shifting understanding, namely function replacement. The knock-down system in the installation was made based on the artist's will or on the art viewers, display areas and the surrounding. In the name of deconstruction, the writer believes that the created arts are multi-interpretable. Key words: deconstruction, installation art and interpretation